SCREENING AND PARTIAL CHARACTERIZATION OF BACTERIOCIN FROM LACTID ACID BACTERIA ISOLATED FROM FAN PALM SUGAR (Borassus flabellifer L) - Prestasia Budi Lestari; Agustin Krisna Wardani (UPT Penerbitan Universitas Jember, 2012)
Bacteriocin is a protein compound that has bactericidal action against microorganism. Bacteriocins from lactid acid bacteria are very potensial as natural food biopreservatives.The aim of this present study is to obtain the isolate of lactic acid bacteria which has apotential to produce bacteriocin from fan palm sugar, to attain the bacteriocincharacterization such as its stability against heat and proteolytic enzyme. Other goal is toobserved the inhibitory activity of bacteriocin against Gram positive and Gram negativebacteria. This research found that 2 isolates LB.9 and LB.30 have a potency to producebacteriocin. LB.9 sensitive to protease enzyme and heat labile whereas isolate LB.30sensitive to protease enzyme and heat stable. The bacteriocin are able to inhibit the growthof Gram positive and Gram negative bacteria.